Long-term impact of living with an obturator following a maxillectomy: A qualitative study. (November 2019) - Semple, Cherith J.; Rutherford, Helen; Killough, Simon; Moore, Ciaran; McKenna, Gerry
Abstract: Objectives: To explore the long-term impact for patients living with an obturator prosthesis, following a maxillectomy for a head and neck neoplasm. Methods: A qualitative approach was employed, using semi-structured interviews. A purposive sample of eight men and four women, living with an obturator prosthesis for at least five years, were recruited. Interviews were digitally recorded and transcribed. Using thematic analysis, two researchers analysed the data. Results: The data were categorised into four themes: 1. Preparedness for living with an obturator, 2. Impact of living with an obturator – what changes to expect, 3. Stability and retention of the obturator, and 4. Coping strategies to aid adjustment. Long-term effects of living with an obturator spanned many aspects of life to include: chewing and eating, speaking, dealing with nasal leakage and altered body image, employment and intimacy issues, along with embarrassment during social encounters. Optimal retention and stability of the obturator, as perceived by the patient, lead to improved social confidence and engagement. The emotional impact varied greatly on peoples' lives. Conclusions: Patients experiencing the greatest long-term challenges had larger defects, were of employment age and had not returned to work. Gaining an improved understanding of the psychology of coping overtime is clearly important, as this can inform interventions to facilitate adjustment for those who are emotionally struggling. Furthermore, the findings of this study could inform the design of a communication tool to facilitate shared-decision making and aid preparedness for living with an obturator following a maxillectomy. Clinical significance: The multidisciplinary head and neck team should provide patients with detailed pre-operative information, including potential effects on social, work and personal relationships. The restorative dentistry team has a pivotal role in the long-term management of these patients, as obturators have a finite lifespan with ongoing maintenance necessary to promote optimal retention and stability.